2017
DOI: 10.3389/fmicb.2016.02159
|View full text |Cite
|
Sign up to set email alerts
|

Horizontal and Vertical Distributions of Transparent Exopolymer Particles (TEP) in the NW Mediterranean Sea Are Linked to Chlorophyll a and O2 Variability

Abstract: Transparent Exopolymer Particles (TEP) are relevant in particle and carbon fluxes in the ocean, and have economic impact in the desalination industry affecting reverse osmosis membrane fouling. However, general models of their occurrence and dynamics are not yet possible because of the poorly known co-variations with other physical and biological variables. Here, we describe TEP distributions in the NW Mediterranean Sea during late spring 2012, along perpendicular and parallel transects to the Catalan coast. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
19
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 54 publications
4
19
1
Order By: Relevance
“…Ortega-Retuerta et al (2010) already reported elevated TEP / Chl a ratios during early summer in the Mediterranean Sea, with values comparable to those we observe at the Faro Cap Ses Salines.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…Ortega-Retuerta et al (2010) already reported elevated TEP / Chl a ratios during early summer in the Mediterranean Sea, with values comparable to those we observe at the Faro Cap Ses Salines.…”
Section: Discussionsupporting
confidence: 91%
“…These observations suggest that P. oceanica meadows, the dominant ecosystem in Mediterranean coastal waters, are an important source of TEP precursors in the Mediterranean Sea (Ortega-Retuerta et al, 2010). Considering the average leaf production of P. oceanica of 876 g DW m −2 y −1 (Duarte and Chiscano, 1999), the estimated 37 000 km 2 covered by P. oceanica in the Mediterranean Sea (range 31 040 to 43 550 km 2 , Marbà et al, 2014) and the average TEP yield from leaf litter experimentally derived here (2344 µg C g DW −1 ), we calculated that P. oceanica releases about 76 Gg C as TEPs annually to the Mediterranean Sea.…”
Section: Discussionmentioning
confidence: 83%
See 3 more Smart Citations